Pharmacoeconomic analysis of tiotropium bromide and olodaterol fixed combination as maintenance therapy for patients with COPD in the Russian Federation - S. V. Nedogoda; M. Yu. Frolov; A. S. Salasyuk; I. N. Barykina; V. O. Smirnova (IRBIS LLC, 2020)
Aim. To assess the economic efficacy of a fixed combination tiotropium bromide+olodaterol (T+O) in comparison with other medications, included in the Vital and Essential Drugs List (VEDL), for the maintenance triple therapy of chronic obstructive pulmonary disease (COPD).Materials and Methods. A Markov model was used for the estimation of direct medical costs associated with different medications. Costminimization and budget impact analyses were performed.Results. The drug costs for T+O were the lowest among all compared treatment strategies. The cost savings in favor of T+O were 24.82% [15.86-29.95%]. The application of T+O strategy in 4,101 target patients led to a decrease in the total direct medical costs under the state programs of guarantees of free medical care by 13.13% in 3 years, which will make T+O therapy available to 643 more patients in the first year and 1,624 patients in three years.Conclusion. A fixed combination T+O is a preferred efficient option for maintenance triple treatment for patients with COPD in comparison with other drugs from VEDL, because it is associated with lower total costs and equal efficacy.